A nonlocal extension of the Wentzel field model in the clothed-particle representation - Shebeko, A.V.; Frolov, P.A. (Вопросы атомной науки и техники, 2012)
The clothed particle approach is applied to express the total Hamiltonian of interacting fields in terms of clothed particles. In order to avoid ultraviolet divergences typical of many field theories we introduce some covariant cutoff functions in momentum space in the Wentzel field model. We will show how in the framework of the nonlocal meson-boson field model one can build interactions between the clothed mesons and bosons. Moreover, the mass renormalization terms, that are compulsory to ensure the relativistic invariance of the theory as a whole (in Dirac's sense), turn out to be expressed through certain covariant integrals. They are convergent in the field model with appropriate cutoff factors.